APPLICATION SYSTEM NURUL HIDAYAH SAVINGS USING MICROSOFT ACCESS 2000 - Dyah Murthiwi (Jurnal Sistem Informasi, 2004)
With existence of computerized system is expected to be faster in services related to accessing savings and the search for savings, compared with the manual method. In order to Nurul Hidayah mosque Mandiri Savings can run well, then the required information and reports of the concrete, such as weekly reports, reports of savings per depositor, as well as lists of depositors.This can be done with the computerization of Independent Savings have been accessed before, and storage of data and calculation of the total savings can be implemented quickly with the help of computer media through the Microsoft Access 2000.